Efektivitas Program 3r (Reduce, Reuse, Recycle) Dalam Mengatasi Permasalahan Sampah Plastik di Surabaya - Ajeng Anindya Murtini; Dida Rahmadanik (Lembaga Pengembangan Kinerja Dosen, 2024)
The 3R program (reduce, reuse, recycle) is one of the programs of the Surabaya City Environmental Office in managing waste problems in Surabaya. With the population density in Surabaya, it does not rule out the possibility of a large number of waste consumption, especially plastic waste. This study aims to see the level of effectiveness of the implementation of the 3R program (reduce, reuse, recycle) in Surabaya City by the Surabaya City Environmental Office. The author looks at DLH Surabaya's efforts in improving the quality of waste management, especially plastic waste and sees what factors support the success of the 3R program in processing plastic waste in Surabaya. Plastic waste has a nature that is difficult to decompose and requires a long time even hundreds of years to decompose. Therefore, DLH Surabaya applies waste management with the 3R concept. The method used in this study is descriptive evaluative. The results of the author's research during his internship at DLH Surabaya show that waste management using the 3R concept (reduce, reuse, recycle) runs effectively as evidenced by the reduction of waste in Surabaya by around 1.5 tons of waste per day and 2 tons of plastic waste per day. The author examines using effectiveness theory according to Sugiyono in Budianni, which includes 3 effectiveness indicators, namely, Target accuracy, Socialization, Monitoring.